Dilema Mahasiswa Mengantuk Saat Kuliah: Solusi untuk Meningkatkan Kualitas Pembelajaran - Febri, Hendrikson (Majalah Ilmiah METHODA, 2024)
The phenomenon of students feeling sleepy during lectures is a common issue that can negatively impact the quality of learning. Several factors contribute to this problem, including excessive gaming habits, social media usage, delays in submitting academic assignments, low attendance in class, and a decline in academic performance. This study aims to identify the factors causing drowsiness among students during lectures and provide solutions to enhance the quality of learning. The research method used is qualitative with a phenomenological approach. The results indicate that students experience sleepiness due to insufficient sleep, monotonous teaching methods, unsuitable lecture times, lack of interaction in the classroom, and inadequate physical conditions of the classroom environment. This research is expected to offer insights and recommendations that are beneficial for educators and educational institutions in creating a more conducive learning environment.